2015
DOI: 10.1007/s12035-015-9148-8
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocatalytic Antiaggregation Activity of Antibodies: Immunoglobulins can Influence α-Synuclein Aggregation at Substoichiometric Concentrations

Abstract: Protein aggregation is involved in a variety of diseases. Alteration of the aggregation pathway, either to produce less toxic structures or to increase aggregate clearance, is a promising therapeutic route. Both active and passive immunization has been used for this purpose. However, the mechanism of action of antibodies on protein aggregates is not completely clear especially given poor ability of antibodies to cross blood-brain barrier. Here, we have shown that antibodies can interfere with protein aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Recent observations by Breydo et al have shown that antibodies can interfere with protein aggregation at substoichiometric concentrations [54]. Interestingly, Inhibition was especially effective in the absence of seeds indicating that early stages in the aggregation pathway were the major targets of the antibody binding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations by Breydo et al have shown that antibodies can interfere with protein aggregation at substoichiometric concentrations [54]. Interestingly, Inhibition was especially effective in the absence of seeds indicating that early stages in the aggregation pathway were the major targets of the antibody binding.…”
Section: Discussionmentioning
confidence: 99%
“…In analogy to our CsgC results, non-canonical ( i . e ., transient) interactions with α-synuclein monomers have been reported for DnaK that resulted in amyloid inhibition [ 38 ] and the anti-aggregation activity by antibodies on α-synuclein was reported to take place via a pseudo-catalytic mechanism [ 39 ]. In similarity to the CsgE results, FKBP12 was suggested to enhance α-synuclein aggregation via a catalytic mechanism involving transient interactions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of unfolded monomeric -Synuclein into the fibrillar state occurs through a complex process involving formation of a premolten globule-like partially folded intermediate followed by the formation of an amyloidogenic nucleus and subsequent oligomerization and formation of protofibrils and fibrils. A common characteristic of these intermediates is the presence of substantial nonpolar patches which cause increased hydrophobic interaction between the molecules, resulting in aggregation [2][3][4][5][6][7][8][9][10]. Since protein aggregates can be observed before the onset of disease symptoms in neurodegenerative diseases, protein aggregation is a relevant target in the development of treatments and diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%